Development and characterization of an innovative drug delivery platform targeting breast cancer brain metastases - Romão, Joana Raquel Aniceto (2022)
Tese de mestrado, Biologia Molecular e Genética , 2022, Universidade de Lisboa, Faculdade de Ciências